The The Stunting Prevention Counseling Through Early Detection and Management of Pregnancy Disorders in Sukahaji Village, Sukawening, Garut - Atun Qowiyyah; Irfan Hilman; Hasnaa Luthfiyyah; Aghna Urfa; Elpan Gustian Permana; Siti Sarah; Nayla Rahmiyya Rizalianti; Yasmina Rihada Humaira; Risa Asvia Afifah; Fahmi Fauziyah; Sumi Sulfia Kartika; Annisa Nuraini; Wildan Rahman; Nazwa Alifah Syahla; Ananda Sofyan; Shintya Nur Fazri; Sri Astuti Adiningsih; Angga Paridwan; Ariel Hasnan Januar; Ade Saefulloh; Syehhabudin Abdulloh; Elfa Widiyanto Nugraha (Indonesian Journal of Community Empowerment (IJCE), 2026)
Stunting remains a major public health issue in Indonesia. In Sukahaji Village, 56 stunted children, 8 infant deaths, and 48 pregnant women at risk were recorded due to inadequate nutrition and maternal health monitoring. This activity aimed to improve the knowledge of pregnant women, prospective mothers, and health cadres regarding nutrition, pregnancy care, and early stunting prevention. Health education was conducted using a participatory approach through lectures, discussions, Q&A sessions, and educational media. Evaluation was carried out using pretest and postest instruments. Participants’ knowledge significantly improved; the “good” category increased frpm 31% to 69%, while the “poor” category decreased from 25% to 6%. Participatory health education effectively improved knowledge and has strategic implications for preventing stunting and reducing infant mortality in Sukahaji Village.